2018
DOI: 10.1089/zeb.2018.1612
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Chromosome Evolution in Hypostominae Tribes (Siluriformes: Loricariidae): Correlation of Chromosomal Data with Morphological and Molecular Phylogenies

Abstract: Hypostominae is the largest subfamily of Loricariidae, and is widely distributed throughout the Neotropic. In the present article, we analyze three Loricariidae species that were considered part of Hypostominae, from three different tribes, to discuss chromosome evolution in this fish group and to review the existent data for the subfamily. Rhinelepis aspera had 54 chromosomes (20m + 26sm+8st), whereas Pterygoplichthys ambrosettii and Megalancistrus parananus had 52 chromosomes, with 16m+24sm+8st+4a and 18m+24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…In addition, Ancistrini species exhibit great differences in terms of number and positions of rDNAs sites. For example, a single chromosome pair carrying 18S rDNA is a characteristic shared by all analyzed Ancistrus Kner, 1854 species [Bueno et al, 2018;Glugoski et al, 2020]. On the other hand, Pety et al [2018] found multiple sites for 18S rDNA in Peckoltia species, another genus of Ancistrini.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Ancistrini species exhibit great differences in terms of number and positions of rDNAs sites. For example, a single chromosome pair carrying 18S rDNA is a characteristic shared by all analyzed Ancistrus Kner, 1854 species [Bueno et al, 2018;Glugoski et al, 2020]. On the other hand, Pety et al [2018] found multiple sites for 18S rDNA in Peckoltia species, another genus of Ancistrini.…”
Section: Introductionmentioning
confidence: 97%
“…Several cytogenetic studies involving Ancistrini species point to conservation of the diploid number of 2n = 52 chromosomes [Bueno et al, 2018;Pety et al, 2018;Glugoski et al, 2020], but differences in the karyotype formulae suggest inversions as the primary mechanisms of chromosomal evolution in this group [Ayres-Alves et al, 2017;Bueno et al, 2018]. In addition, Ancistrini species exhibit great differences in terms of number and positions of rDNAs sites.…”
Section: Introductionmentioning
confidence: 99%
“…Several cytogenetic studies in Hypostomus revealed a great complexity and diversity of information [10][11][12][13][14][15][16][17][18][40][41][42][43][44][45][46] , showing extensive karyotype variation in this group. Cytogenetic analysis evidenced 2n = 54 chromosomes as an ancestral characteristic in Loricariidae, since it was reported in the basal genera and in the sister group Trichomycteridae 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis evidenced 2n = 54 chromosomes as an ancestral characteristic in Loricariidae, since it was reported in the basal genera and in the sister group Trichomycteridae 47 . Karyotype analyses in Hypostomus have allowed well-defined evolutionary trends, as the occurrence of high variation in the 2n, due to chromosomal rearrangements, like centric fissions [12][13][14][15][16][17][18][19][20][40][41][42][43][44][45][46] , which could explain the increased 2n present in the H. commersoni (2n = 68 chromosomes), H. derbyi (2n = 68 chromosomes) and H. myersi (2n = 74 chromosomes). Chromosome variability in Hypostomus may be assessed by intraspecific variation of 2n, karyotype formula, heterochromatin localization, and number and localization of NORs sites 15,17,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation